2010
DOI: 10.1371/journal.pone.0011383
|View full text |Cite
|
Sign up to set email alerts
|

Valproate Administered after Traumatic Brain Injury Provides Neuroprotection and Improves Cognitive Function in Rats

Abstract: BackgroundTraumatic brain injury (TBI) initiates a complex series of neurochemical and signaling changes that lead to pathological events including neuronal hyperactivity, excessive glutamate release, inflammation, increased blood-brain barrier (BBB) permeability and cerebral edema, altered gene expression, and neuronal dysfunction. It is believed that a drug combination, or a single drug acting on multiple targets, may be an effective strategy to treat TBI. Valproate, a widely used antiepileptic drug, has a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(139 citation statements)
references
References 72 publications
6
132
1
Order By: Relevance
“…We recently reported that Scriptaid, a novel inhibitor of class I/II HDACs, protects gray matter against experimental TBI (10). These findings are consistent with reports indicating that other HDAC inhibitors can attenuate gray matter injury in TBI models (11)(12)(13)(14). Whether Scriptaid can protect white matter is unclear, however.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…We recently reported that Scriptaid, a novel inhibitor of class I/II HDACs, protects gray matter against experimental TBI (10). These findings are consistent with reports indicating that other HDAC inhibitors can attenuate gray matter injury in TBI models (11)(12)(13)(14). Whether Scriptaid can protect white matter is unclear, however.…”
supporting
confidence: 92%
“…At present, there are no therapies that can cure the cognitive and motor deficits in TBI patients (5,15); however, an increasing number of studies show that HDAC inhibition can ameliorate injury in experimental models of TBI and other diseases, perhaps by modulating gene expression in a cell type-dependent manner (11)(12)(13)(14)24). Taken together with previously reported findings, our present study supports the view that Scriptaid is a suitable therapeutic candidate for trauma-induced mechanical injury and secondary inflammation-induced cell death in both gray and white matter.…”
Section: Discussionmentioning
confidence: 99%
“…A vestibulomotor (beam balance) and a motor skill task (paw placement) were used to determine animals' motor performance on days 1-3 post-treatment, as described previously. 39,[46][47][48] For beam balance, rats were preassessed by placing them on a narrow wooden beam (1.5 cm wide) and measuring the duration they remained on the beam for up to 60 sec. Animals were given repeated training until capable of balancing on the beam for the entire 60-sec period for three consecutive trials.…”
Section: Assessment Of Motor Functionmentioning
confidence: 99%
“…10,35,36 However, long-term dietary supplementation with o-3 PUFAs did not significantly prevent o-3 PUFAs protects against TBI H Pu et al tissue loss at the impact region. Nonetheless, o-3 PUFAs completely abolished neuronal loss in the CA3 region of the hippocampus.…”
Section: Oligodendrocyte Protection Is Mediated Via Direct Effect Andmentioning
confidence: 99%